Concepção de compreensão leitora na prova de Língua Inglesa do ENEM: um enfoque dialógico discursivo - Silva Sobrinho, Ronaldo Alves da (2019)
This research deals with reading comprehension of the verbal-visual utterances that integrate the English language test of the Exame Nacional do Ensino Médio (ENEM) between 2014 and 2017. The objective is to analyze the questions on this exam that brings the verb-visual utterance and to investigate how the ability to comprehend such utterances is required from the candidates/ students. We recognize that such analysis is relevant, since the Curriculum Guidelines for Secondary Education in Foreign Languages (OCEM-LE) focuses on reading for the development of citizenship. The theoretical basis of this research lies in the dialogicaldiscursive perspective of Bakhtin's (1998, 2010, 2011, 2015, 2016) and Circle studies, as well as Brazilian researchers such as Brait (2005, 2010, 2013, 2015), Faraco (2009, 2016), Francelino (2015), among others. This research, when mobilizing reflections on concepts such as dialogism, enunciation, verb-visuality, among others, specifically aims to: a) identify in the alternatives of the questions the type of reading comprehension conceived by the committee that creates them; b) verify how the verb-visual utterance is explored; c) identify the reading strategies that students need to mobilize to answer them. This is a documental and qualitative research formed by a corpus formed by six questions containing verb-visual utterance. The results point out that the apprehension of the senses occurs in a passive way, since the focus of the reading strategies is based predominantly on the purely linguistic phenomenon, on the aspects of the utterance that are repeatable and identical, distancing itself from the author’s axiological project. Therefore, we propose for the preparation of future exams a revision of the theoretical-methodological conceptions that support them, so that they will allow the dialogicaldiscursive aspect of the verb-visual utterance to promote a deeper reading and comprehension.